A Three lncRNA Set: AC009975.1, POTEH-AS1 and AL390243.1 as Nodal Efficacy Biomarker of Neoadjuvant Therapy for HER-2 Positive Breast Cancer - Bi, Zhao; Qiu, Peng-Fei; Zhang, Yue; Song, Xing-Guo; Chen, Peng; Xie, Li; Wang, Yong-Sheng; Song, Xian-Rang (Frontiers in Oncology, 2021)
Purpose: The aim was to explore whether the expression of lncRNAs in primary tumor could predict nodal efficacy after neoadjuvant therapy (NAT) for HER2+ breast cancer. Methods: Total RNA was extracted from HER2+ breast cancer tissues before NAT (n=103), as well as from 48 pairs of cancers and para-cancers tissues which did not receive NAT. Different lncRNAs were selected by microarray, validated by qPCR, and analyzed to illuminate its potential as nodal efficacy biomarkers after NAT. Results: Our results demonstrated that three lncRNA sets: lncRNA-AL390243.1, POTEH-AS1, and lncRNA-AC009975.1 were up-regulated in non-apCR tissues, the AUC value was 0.789 (95%CI: 0.703-0.876). The multivariate logistic regression analysis identified the expression of lncRNA-AL390243.1 (OR 5.143; 95% CI: 1.570-16.847), tumor type (OR 0.144; 95% CI: 0.024-0.855) and nodal stage (OR 0.507; 95% CI: 0.289-0.888) as independent predictors for apCR after NAT in HER2+ patients (all p<0.05). Then the three predictors were used to create a predictive nomogram. The AUC value was 0.859 (95%CI: 0.790-0.929). The calibration curve showed a satisfactory fit between predictive and actual observation based on internal validation with a bootstrap resampling frequency of 1000. Patients with higher expression of lncRNA-AL390243.1 had a worse survival. LncRNA-AL390243.1 was up-regulated in nodal positive subgroup than in nodal negative subgroup (p=0.0271). Conclusion: The lncRNA-AL390243.1, POTEH-AS1, and lncRNA-AC009975.1 were upregulated in non-apCR breast cancer tissues. These three lncRNAs might have the potential to be used as predictive biomarkers of nodal efficacy of HER2+ breast cancer. The underlying molecular mechanisms needs further studies to illuminate.